“Deductive and Inductive methods influence to teach grammar in the English language learning in the students of 10th of Educación General Básica, class “A” at “Camilo Gallegos Toledo” High School, Chimborazo province in the academic year 2016-2017” - Lema Miranda, Marcia Cecilia (2017)
Most of the students make many grammatical mistakes as a consequence, students lack a good grammatical structure, therefore the objective of the thesis was to determine the reasons why students make many grammatical errors considering the influence of deductive and inductive methods applied by the teacher to teach grammar in English language learning. Besides, it was researched the strategies used by the teacher to correct students' errors. This research was qualitative, descriptive and exploratory where the method used to describe and analyze the behavior of the population was the ethnographic. The data were obtained through direct observation technique whose instruments were observation guides carried out at the “Camilo Gallegos Toledo” High School, Chimborazo province, Riobamba city, with 37 students of 10th of Educación General Básica, class “A” during the month of November 2016, which contained seven items related to the objectives, each one directed to the teacher and students in order to collect information. In the research, it was determined that the teacher did not apply adequately the methods to teach grammar and did not use strategies to correct errors made by students. On the other hand, it was noted that students did not reflect on how a structure is formed and how it is used, then students need help from their teacher to improve their grammar learning as well as an extensive practice using real situations to students discover the grammatical rules by themselves to achieve a meaningful learning.